(untitled) (Journal of Nobel Medical College, 2013)
Background/ Aim: Very few reports exist regarding the causes of ocular morbidity in western Nepal. The study is performed to identify the causes of ocular morbidity in a clinic at Waling in western Nepal. Method: A retrospective study of all patients attending the eye clinic at Waling from August 2010 to August 2011 was done. Result: The study included 915 patients, 617 (67.5%) females, and 298 (32.5 %) males. Refractive error was the most common ocular morbidity accounting 26.8% followed by conjunctivitis 20.6%, cataract 11.8%, pterygium 6%, chalazion/stye 4%, ectropion/entropion 3.9%, keratitis 3.8%, dry eyes 2.8%, and corneal opacities 2.3%. Conclusion: The study gives a picture of pattern of ocular disease in western Nepal which is helpful in planning & management. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 27-30 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7669